Synthetic and Non-synthetic Cannabinoid Drugs and Their Adverse Effects-A Review From Public Health Prospective - Cohen, Koby; Weinstein, Aviv M. (Frontiers in Public Health, 2018)
There is a growing use of novel psychoactive substances containing synthetic cannabinoids. Synthetic cannabinoid products have effects similar to those of natural cannabis, yet, these drugs are more potent and dangerous, and have been associated with dangerous adverse effects. Here, we review current literature on the epidemiology, acute, and chronic effects of synthetic and natural cannabinoid-based drugs. Synthetic drugs contain a mixture of psychoactive compounds that mostly bind cannabinoid receptors with high potency. These synthetic drugs replicate the effects of natural cannabis and Δ9-tetrahydrocannabinol but they induce more severe adverse effects including respiratory difficulties, hypertension, tachycardia, chest pain, muscle twitches, acute renal failure, anxiety, agitation, psychosis, suicidal ideation, and cognitive impairment. Chronic use of synthetic cannabinoids has been associated with serious psychiatric and medical conditions and even death. Given the growing popularity in the use of cannabinoid-based drugs and their harmful potential, there is a need for further research in this field.